Thermochemical splitting of CO2 using solution combustion synthesized lanthanum–strontium–manganese perovskites - Gorakshnath Takalkar (14151135) (2021)
Redox reactivity of La(1-x)SrxMnO3 (LSM) perovskites towards a solar thermochemical CO2 splitting (CS) cycle is investigated. The LSM perovskites are synthesized via a solution combustion synthesis (SCS) method using glycine as the reducing agent. Multiple analytical techniques are used for the structural characterization of the LSM perovskites. Thermogravimetric thermal reduction (TR) and CS cycles (in three sets: one, three and ten cycles) are conducted to estimate the amounts of O2 released (nO2 ) and CO produced (nCO) by each LSM perovskite. Higher nO2 by each LSM perovskite, as compared to the nCO during the first cycle. The nO2 is decreased, and the re-oxidation capacity of each LSM perovskite is improved from cycle one to three. In terms of the average nO2 and nCO from cycle 2 to cycle 10, the La0.60Sr0.41Mn0.99O2.993 (214.8 μmol of O2/g⋅cycle) and La0.30Sr0.70Mn0.99O2.982 perovskites (342.1 μmol of CO/g⋅cycle) are observed to have the uppermost redox reactivity. The redox reactivity of all the LSM perovskites (except for La0.88Sr0.11Mn1.00O2.980) is recorded to be higher than that of the widely studied CeO2 material. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2020.119154